2010
DOI: 10.1186/1756-0500-3-113
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length, pre-eclampsia, and gestational diabetes

Abstract: BackgroundTelomere length is a marker of cumulative damage to the cell, and has been associated with cardiovascular disease, hypertension, and diabetes.FindingsThe association of telomere length with pre-eclampsia and gestational diabetes mellitus (GDM) was examined in a nested case-control study. Circulating leukocyte telomere length was measured by Quantitative-PCR. Mean and median telomere length among cases and controls was compared, and logistic regression was used to model the outcomes as a function of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 37 publications
(51 reference statements)
2
19
0
Order By: Relevance
“…Harville et al . 15 showed a trend of shorter telomeres in women with GDM, although the association was not statistically significant, which may be explained by the limited sample size, or the variability of leukocyte between individuals. Several previous studies also reported that reduced leukocyte telomere length was associated with incident diabetes risk 12,13 .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Harville et al . 15 showed a trend of shorter telomeres in women with GDM, although the association was not statistically significant, which may be explained by the limited sample size, or the variability of leukocyte between individuals. Several previous studies also reported that reduced leukocyte telomere length was associated with incident diabetes risk 12,13 .…”
Section: Discussionmentioning
confidence: 74%
“…Hyperglycemia in diabetes status is known to increase oxidative stress, and then accelerates the telomere length shortening 14 . However, the studies involved in association between telomere length and gestational diabetes mellitus (GDM) are scarce 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, pregnancies in mothers with GDM and with type 1 diabetes have been associated with increased telomerase activity in cord blood [30]. Other studies have, however, reported no association between GDM and cord blood telomere length [31] or between maternal type 1 diabetes and telomere length in young adult offspring [32]. Importantly, these studies were mainly of small sample size and, to the best of our knowledge, the effect of GDM on telomere length in adolescent offspring has not previously been reported.…”
Section: Introductionmentioning
confidence: 99%
“…We have not shown, in this study, whether the shortened telomeres were inherited by the offspring. While some studies suggest that this is the case [16, 17], other studies find no such association [1820]. This may be due to the technical challenges imposed by the use of leukocyte DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, individuals may start life with shorter than normal telomeres that then play a role in the disease progression of diabetes [14], contributing to impaired glucose management and insulin secretion [15]. The latter possibility is indicated by the observation that diabetes during pregnancy, is linked to shortened telomere length in blood leukocytes from exposed children [16, 17], although not all studies report such a link [1820]. If individuals exposed in utero to GDM start life with shorter telomeres, this may explain why they are at higher risk of adverse outcomes such as T2DM later in life.…”
Section: Introductionmentioning
confidence: 99%